(untitled) (Research, Society and Development, 2020)
The occupational health and safety management system (OHSMS) has as its main aspect the adoption of control measures focused on the prevention of injuries and illnesses through the promotion of safe and healthy workplaces. The objective of this study is to present the main steps for implementing an OHSMS, based on the international standard ISO 45001. During the implementation, several strategies can be implemented by the organization to structure the management system. Regardless of the strategy adopted, the satisfactory performance of an OHSMS is directly associated with the role of senior management, which must demonstrate leadership and commitment. In addition, it must ensure that responsibilities and authorities for relevant roles in the OHSMS are assigned and communicated at all levels and functions of the organization. The methodology used in the study was bibliographic survey, documentary research and practical case studies of implementation. As a final result, the main key factors for the implementation of an OHSMS are presented, in an effective and consistent manner, and in line with the requirements of ISO 45001.